The level of physical activity in the lifestyle of physical education students - Południak, Natalia; Rykiel, Zuzanna; Pelic, Paulina; Szymańska, Natalia; Drzewi, Dominik; Chrzanowski, Michał; Suchowicz, Katarzyna; Czerw, Piotr; Burakowska, Justyna; Skrzek, Daria; Rejman, Aneta (Journal of Education, Health and Sport, 2021)
Subject: The level of physical activity in the lifestyle of physical education students Introduction: Physical activity is defined as voluntary and spontaneous physical activity practiced during leisure time. Thanks to it, the body can function properly and develop on many levels. It plays an important role in social and physical development, as well as intellectual and emotional development. It finds its place in the fight against civilization diseases, it is also beneficial in resisting many other diseases. Aim: The aim of the article is to assess the level of physical activity of physical education students of various specializations. Material and methods: The research was conducted among students of physical education at the University of Rzeszów. 60 people took part in them - 38 women and 22 men aged 19-30. The respondents answered anonymously to 18 closed, single-choice questions. Results: The majority of students are engaged in physical activity outside a college, and 65% of it is at amateur level activity. The most common reason why respondents take up physical activity is to improve the functional fitness of the body. 58% of the respondents undertook physical activity more than 3 times a week. Conclusions: Most of the respondents do physical activity outside of their studies. The most common reason for taking up physical activity among the respondents was the improvement of the functional fitness of the body, and the factors influencing the fact that students are physically active were to the greatest extent sports activities